The Effect of Stock Ownership Toward the Corporate Social Responsibility (CSR) Disclosure - Nurani Hartikayanti, H; Wicaksana Siregar, I (KnE Social Sciences, 2018)
This study aims at investigating the effect of stock ownership by foreign parties and government toward the level of corporate social responsibility (CSR) disclosure. The participating companies of Indonesia Sustainability Reporting Awards 2015 were selected as the samples by employing purposive sampling technique. This study employed secondary data from annual report, sustainability report, and financial report. Data were analyzed using simple linear regression analysis. The result shows that government and foreign ownership had no significant influence toward CSR disclosure. Keywords: government ownership, foreign ownership, Indonesia sustainability, reporting awards, corporate social responsibility